2020
DOI: 10.3389/fpsyg.2020.02060
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Abilities of Adults’ With Down Syndrome as a Window to Their Morphosyntactic, Socio-Cognitive, and Prosodic Abilities

Abstract: Down syndrome (DS) is the most common developmental disorder characterized by mild to moderate intellectual disability. Several studies have reported poor language and prosodic skills and contradictory results regarding individuals' with DS sociocognitive skills, whereas most of them have focused on children with DS. The present study attempts to explore adults' with DS language, socio-cognitive and prosodic abilities via the use of story-retellings. Twenty adults with DS and two groups of TD children, one mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 94 publications
(163 reference statements)
4
17
1
1
Order By: Relevance
“…Our findings are consistent with the findings of Grela (2002) who also described similarities of MSV production in a small group of seven children with DS and seven TD children matched by MLU. Our finding of mental-age appropriate production of MSV in individuals with DS is, however, in contrast to the studies of Channell (2020), who described impaired performance of MSV production in her participants with DS in a similar narration task, and Martzoukou et al (2020), who found poorer use of internal state terms in individuals with DS than in cognition-matched TD children. While Channell did not include a control group of TD children against which performance of the DS group could be measured and evaluated as mental-age appropriate, the discrepancy to the findings of Martzoukou et al (2020) awaits explanation.…”
Section: Number and Proportion Of Msvcontrasting
confidence: 99%
See 4 more Smart Citations
“…Our findings are consistent with the findings of Grela (2002) who also described similarities of MSV production in a small group of seven children with DS and seven TD children matched by MLU. Our finding of mental-age appropriate production of MSV in individuals with DS is, however, in contrast to the studies of Channell (2020), who described impaired performance of MSV production in her participants with DS in a similar narration task, and Martzoukou et al (2020), who found poorer use of internal state terms in individuals with DS than in cognition-matched TD children. While Channell did not include a control group of TD children against which performance of the DS group could be measured and evaluated as mental-age appropriate, the discrepancy to the findings of Martzoukou et al (2020) awaits explanation.…”
Section: Number and Proportion Of Msvcontrasting
confidence: 99%
“…Specifically, it does not hinge on the acquisition of subordinate or complement clauses. Our finding that the ability to express perspective taking via MSV use is not dependent on syntactic abilities is also supported by Martzoukou et al (2020) who found morpho-syntactic abilities as measured by a sentence-repetition not to be related to the use of internal state terms.…”
Section: Relations Between Msv Production and Language Variablessupporting
confidence: 84%
See 3 more Smart Citations